Histological Study of Stomach in (Mallard) Anas platyrhynchos - Al-Helali, Sh. R.; Al-Sudani, A. A.; Jaber, R. J. (Ibn AL-Haitham Journal For Pure and Applied Sciences, 2016)
This search aim to study the histological structure of Stomach of domestic duck Anas platyrhynchos. Six healthy birds (males and females) are used and after their slaughter the abdominal region was carefully opened and the stomach separated from it's connection with alimentary canal, cleaned with water and fixed  in 10% formalin. The histological study showed that the wall of the glandular and muscular stomach consist of four tunicae:Tunica Mucosa,Tunica Submucosa,Tunica Muscularis and Tunica Serosa. The results suggested that the Muscularis mucosa layer represented the secretary part of glandular stomach, the keratinoid material lining the lumen of gizzard, and the tunica muscularis was the thickest one among four tunicae.